Substitution of Mannan-Binding Lectin (MBL)-Deficient Serum With Recombinant MBL Results in the Formation of New MBL/MBL-Associated Serine Protease Complexes - Keizer, Mischa P.; Kamp, Angela; van Mierlo, Gerard; Kuijpers, Taco W.; Wouters, Diana (Frontiers in Immunology, 2018)
The lectin pathway (LP) of complement activation depends on the activation of the MBL-associated serine proteases (MASPs) circulating in complex with mannan-binding lectin (MBL). MBL deficiency is the most common complement deficiency and has been associated with several pathological conditions. As we had previously shown, plasma-derived MBL (pdMBL) contains pre-activated MASPs that upon in vivo pdMBL substitution results in restoration of MBL concentrations but no LP functionality due to immediate inactivation of pdMBL–MASP complexes upon infusion. In this study, we analyzed MBL-sufficient and -deficient serum by size-exclusion chromatography for complexes of LP activation. In both sera, we identified non-bound free forms of MASP-2 and to lesser extent MASP-1/3. After addition of recombinant MBL (rMBL) to MBL-deficient serum, these free MASPs were much less abundantly present, which is highly suggestive for the formation of high-molecular complexes that could still become activated upon subsequent ligand binding as shown by a restoration of C4-deposition of MBL-deficient serum. Ficolin (FCN)-associated MASPs have been described to redistribute to ligand-bound MBL, hereby forming new MBL/MASP complexes. However, reconstitution of MBL-deficient serum with rMBL did not change the relative size of the FCN molecules suggestive for a limited redistribution in fluid phase of already formed complexes. Our findings demonstrate that rMBL can associate with free non-bound MASPs in fluid phase while preserving full restoration of LP functionality. In contrast to pdMBL products containing pre-activated MASPs which become inactivated almost immediately, these current data provide a rationale for substitution studies using rMBL instead.